Comparing stabilization plans of Argentina, Brazil and Peru - Arellano, José Pablo (1987)
​This paper sets out to identify the main differences and simmilarities between the Stabilization Plans of Argentina, Brazil, and Perú, as well as making some remarks on anti-inflationary policies. The author also analyzes the initial success of these programmes in terms of their handling of inflation and its subsequent regression. It concludes that the greatest and most important potential cost of a stabilization programme can be measured in terms of its impact on the economic activity, and the levels of employment that it genders. Heterodox plans have not had these costs while achieving a "relative stabilization", but have. on the contrary, managed to increase production. Contrarily, the orthodox alternative tums out to be very costly in the case ofrebellious inflation, since it does not act directly over the inertia.